FISHERIES AGRO-BUSINESS DEVELOPMENT AS A STRATEGY IN IMPROVING FISHERIES ECONOMY POST COVID 19 USING FROZEN FILLET PRODUCTS SYSTEM - Doni Ferdiansyah; Sawiyah Sawiyah; Abdul Qadir Jailani (International Journal of Economy, Education and Entrepreneurship, 2023)
Fillet is one type of ready-to-eat frozen food product. Fillet is made from ground meat, given spices, and a binder mixture, then cured, steamed, cut, and covered with flour adhesive (dough) and bread flour (breading). Field Work Practice is to study and learn workers' personal hygiene in producing Fillets of dumbo catfish (Clarias gariepenus) at P2MKP Karya Lestari, Pamekasan. This Riset Activity uses the descriptive observative method, which is a method of solving a problem by describing and explaining the situation and condition of an object of observation based on direct observations and facts that occur in the field. Collection in this Risetactivity uses primary collection methods from interviews, active participation, observations, and secondary through literature study. The application of personal hygiene in P2MKP has been carried out well by standards, including using closed clothing, using gloves according to standards, maintaining the health and safety of workers, and prohibiting the use of personal equipment made of metal. But the knowledge of personal hygiene workers is not evenly distributed because some workers have yet to receive training facilities on personal hygiene, which is an obstacle in applying personal hygiene to workers